(untitled) (Italian Journal of Public Health, 2012)
Migration, both within and between countries, has increased worldwide in recent years. While migration in itself need not present a risk to health, it is often characterized by increased stress and individual vulnerability to disease and inequalities in access to care. Migrants from high tuberculosis (TB) prevalence countries may be at risk of TB before leaving their country, during travel and after resettlement. In many high-income countries, more than half of the TB cases emerging today occur in patients born in another country. In less affluent countries, shifts in TB epidemiology associated with population movements are also being reported. Foreign-born persons often face several barriers to care in a new country as a result of inadequate knowledge of, or coverage by, the health care services, differences in culture and language, lack of money, comorbidity, concern about discrimination and fear of expulsion. National authorities apply different policies to screen migrants for TB and to provide preventive or curative treatment, with varying coverage, yield and effectiveness. If screening is to be of use, it needs to fit into a broader national strategy for TB care and management. Appropriate treatment needs to be provided in a manner conducive to its full completion. This is critical both for the individual patient and for public health. We discuss the main associations between TB and migration based on data from recent publications on surveillance, policy and practice.